Systemic lupus erythematosus and chronic myeloid leukemia: mere coexistence or association? - Rudrajit Paul, Jayanti Ray, Babulal Daulagajao, Rojina Choudhury, Sanjoy Bhattacharya (Journal of Applied Pharmaceutical Science, 2014)
Systemic Lupus Erythematosus (SLE) is a multisystem connective tissue disorder associated with increased predisposition to haematological malignancies. Myeloid series malignancies are rarely associated with SLE. We here report a case of Philadelphia chromosome positive chronic myeloid leukemia (CML) associated with SLE in a 36 year old Indian housewife. This is probably the first such case to be reported from India and only a handful of such cases have been reported in World literature till now. The patient presented initially with leukopenia. She was treated with imatinib with good results.
Keywords: SLE, CML, imatinib, eosinophilia, myeloid malignancy.